Geographical distribution, characterisation and evaluation of Saccharomyces cerevisiae strains isolated from South African vineyards in the warmer, inland regions of the Western Cape - Khan, Wesaal (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1999.